ENHANCING ENGLISH LANGUAGE LEARNING AT SMK N 2 PACITAN THROUGH THE UTILIZATION OF THE CAKE APPLICATION - Rika Nurcahyani; syafiqoh, Dzi Syafiqoh; Ucik Intan Sholeha; Rohmatul Ummah; Erna Setyowati (The Journal Of English Teaching For Young And Adult Learners, 2024)
Language learning is very important in preparing students for success in a globalized world. As technology continues to transform education, innovative approaches are being explored to make learning more accessible and engaging. This article explores the integration of the Cake application, a language-learning tool, into the classroom environment at SMK N 2 Pacitan. The research was conducted on October 16, 2023. This article reviews the existing literature on the benefits and challenges of using like-minded applications in education, emphasizing increased engagement, experiential learning, and collaborative opportunities. It also addresses potential challenges such as technical requirements and pedagogical integration. The research method used included class observation and interviews with students, revealing positive student perceptions and experiences with the Cake application. The findings show that students find the application interesting and easy to use, and it has a positive impact on their language skills and vocabulary. Additionally, students expressed an intention to continue using the application and recommend it to others. While advantages such as combining learning with play were highlighted, some disadvantages, including in-app advertising and internet data requirements, were also identified. Overall, this article provides insight into the benefits and challenges of using the Cake application in language learning, offering a valuable foundation for further research and practical application in educational settings.